Gender Impact of Chasing Dirty Money Policies: A Fantasy Pitch - Bao Hoang Nguyen; Jia Chen (Journal of Accounting and Management Information Systems (JAMIS), 2017)
This paper describes the use of the fantasy research pitching exercise in the context of the UQ Summer Research Program. The authors provide their personal reflections on the process of doing the exercise and highlight the role of Faff's (2015, 2017) pitching research template as a useful research learning tool.
Keywords: J16; K42; 650; Pitching Research; Fantasy Pitching; Gender; Dirty Money